Factors related to Severity of injuried in patients with traffic accidents at Trauma and Emergency Ward, Thammasat University Hospital - Thummaraksa, Thida; Laptavee, Booppha; Kanlerd, Amonpon (Thammasat University Hospital Journal Online, 2016)
The purposes of this study were to study factors related to severity of injured from traffic accidents at Trauma and Emergency Ward, Thammasat University Hospital (TUH). The sample was 150 injured who were admitted in the period of May to August 2014. And they were selected by specific random sampling. Data was collected by using questionnaire, and records of severity of injuries. And the data were analyzed by using frequency, percentage and chi square test. The results revealed that the most of injured sample was male (68.7%), aged between 15 - 40 years (65.4 %) and they were drivers (52.0%). The cause of injured was hit or collision with other vehicle (47.3%). Motorcycle was used for transport frequently (51.4 %). The characteristic of wound was Blunt trauma (62.0 %). The vehicles ran at the speed 40 – 60 Kilometers per hour (38.0%), and the accidental time was mostly at 6:00 a.m. – 12:00 p.m. (31.3%). The majority of injured did not take alcohol drinking (66.0 %), and they did not use Personal Protective Equipments: PPE (helmet and safety belt) during driving or transport (58.0%). And during driving, they did not use medicine with side effect on the nervous system (78.0%). The severity of injury was at mild level mostly (38.0%). The factors related to the severity of injured from traffic accidents statistically (p ≤ 0.05) were the speed of vehicle, alcohol drinking, PPE (helmet and safety belt) using and the usage of medicine with side effect on the nervous system. Whereas the other factors related to the severity of injured statistically insignificant (P > 0.05), including gender, age, injured category, the cause of injury, vehicle classification, wound characteristics and accidental time. The findings of this study can be utilized as a guideline for prevention and reduce the effects of the traffic accident severity through campaign and detecting traffic violator with high speed driving, alcohol drinking, no PPE (helmet and safety belt) and the usage of medicine with side effect on the nervous system during driving.